Psychological image of childhood characteristic of modern schoolchildren’s parents - A. D. Andreeva (Вестник Мининского университета, 2019)
Introduction: psychological image of childhood is considered as a set of parents’ social representations about the value of childhood as a period of life, the purpose and the point of education, the future they want for their children, social and cultural resources of the family. We have assumed that the subjective image of childhood determines the educational trajectory parents choose for their child and becomes relevant in a situation of choice. We present the results of a three-year-long empirical research on structure and content of social representations about the main components of childhood characteristic of the parents whose children move up to a new stage of education: enter primary school, move to secondary school and graduate from secondary school.Materials and research methods: the research was carried out in the framework of the structural approach by J.-C. Abric, developed in line with the conception by S. Moscovici. As the main methodological technique, we used the method of prototypical analysis of free associations by P. Verges.The results of the research: it has been found out that parents’ psychological image of childhood is stable in the part which is based on the stereotypes and cultural traditions of the society, as well as on their own life experience. Another part of the childhood image, that is more mobile and variable, reflects the changes associated with the age-related needs of the children as well as the parents’ goals.Discussion and conclusion: we have confirmed the hypothesis that parents whose children go to schools that implement educational programs of different complexity have different representations about the values and goals of childhood as a life period. Based on the data received, we have reconstructed descriptive models of childhood image that are characteristic of parents who choose schools with different requirements for children’s intellectual and psychological development: ordinary secondary schools or educational institutions having high rating positions.